B29 Two-point Magnitude Mri For Rapid Mapping Of Brown Adipose Tissue And Its Application To The R6/2 Mouse Model Of Huntingtons Disease. (17th September 2014) - Lindenberg, KS; Weydt, P; Müller, HP; Bornstedt, A; Ludolph, AC; Landwehrmeyer, GB; Rottbauer, W; Kassubek, J; Rasche, V
Abstract : The recent discovery of active brown fat in human adults has led to renewed interest in the role of this key metabolic tissue in health and disease. This is particularly true for Huntington's disease (HD), with a prominent energy deficit phenotype. HD patients show an unintended weight loss with normal or even high food intake already at early stages of the disease. Alterations in brown adipose tissue (BAT) including failure in thermogenesis are found in HD mouse models. Current methods for imaging BAT in vivo are in limited use because they are equipment-wise demanding and often prohibitively expensive. This prompted us to explore how a standard MRI set-up can be modified to visualise BAT in situ by taking advantage of its characteristic fat / water content ratio to differentiate it from surrounding white fat. We present a modified MRI protocol for use on an 11.7 T small animal MRI scanner to visualise and quantify BAT in wild-type and disease model laboratory mice. In this application study using the R6/2 transgenic mouse model of HD we demonstrate a significantly reduced BAT volume in HD mice vs. matched controls (n = 5 per group). This finding provides a plausible structural explanation for the previously described temperature phenotype of HD mice and underscores the significance of peripheral tissue pathology for the HD phenotype. On a more general level, the results demonstrate the feasibility of MR-based BAT imaging in rodents in vivo and open the path towards transferring this imaging approach to human patients. Future studies are needed to determine if this method can be used to track disease progression in HD and other disease entities associated with BAT abnormalities, including metabolic conditions such as obesity, cachexia, and diabetes. Funding: EHDN seed fund 414.